Optical, dielectric and photocatalytic properties of perovskite ZnTiO3 nanoparticle synthesized by sonochemical process - Wattanawikkam, Chakkaphan; Pecharapa, Wisanu (My University, 2015)
The sonochemical method was employed for synthesizing perovskite zinc titanate nanopowders. The yield powders were calcined at 600-900 °C for 2 h. High crystallinity phase of cubic ZnTiO3 was obtained at calcination temperature of 600 °C while mixing phase of cubic and hexagonal was observed in the sample calcined at 700 °C. For the samples calcined at 800 and 900 °C, the hexagonal structure was dominant phase with a trace of rutile TiO2 and spinel Zn2TiO4 phase. X-ray absorption near edge spectroscopy technique (XANES) was used to probe crystal and local structure of the synthesized powders. The samples calcined at 700 °C exhibited the superior photocatalytic performance in decolorization of Rhodamine B dye under ultraviolet irradiation within 75 min. The dielectric permittivity and loss tangent of ZnTiO3 calcined at 700 °C was found to be 20 and <10-2. Effect of calcination temperature on structural, morphology, optical, dielectric properties and photocatalytic activity were also investigated and discussed.
Keywords: nanoparticles; sonochemical method; XANES; ZnTiO3